Keadilan Organisasi dan Kepemimpinan Etis sebagai Determinan Perilaku Inovatif Pegawai pada Organisasi Sektor Publik - Wutlanit, Meisyor Yudi; Bahasoan, Aminah; Rolobessy, Mike J (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This research investigates how perceptions of fairness within the organization and the ethical conduct of leaders shape the innovative capacity of personnel at the South Buru Regency Trade Office. Innovation within this institution is particularly crucial because the agency faces challenges related to distribution networks, supply chain limitations, and the need to improve licensing and trade service processes. Strengthening employees’ innovative capability is therefore essential for enhancing efficiency, supporting regional economic development, and improving public service quality. The study adopts a descriptive-quantitative design with a causal-correlational framework, emphasizing that the independent variables are considered contributors to changes occurring in the dependent variable. The entire workforce of the South Buru Regency Trade Office, consisting of 57 employees, served as the research population, and because the group was relatively small, a saturated sampling technique was applied. Data processing was carried out using multiple linear regression procedures. The findings reveal that: (1) organizational justice provides a measurable contribution to enhancing employees’ innovation capabilities, (2) ethical leadership also plays a significant role in strengthening innovative behavior among employees, and (3) when considered simultaneously, both organizational justice and ethical leadership jointly exert an influence on the innovation ability of employees within the South Buru Regency Trade Office.